"Binary salt" of hexane‐1, 6‐diaminium adipate and "carbon nanotubate" as a synthetic precursor of carbon nanotube/Nylon‐6, 6 hybrid materials. Issue 3 (7th October 2013) - Boncel, Slawomir; Górka, Jacek; Shaffer, Milo S.P.; Koziol, Krzysztof K.K.
<x xml:space="preserve">Abstract</x> A novel chemical approach was established to produce carbon nanotube/Nylon‐6, 6 hybrid materials from readily available substrates, that is, Nylon‐6, 6 salt and oxidized multiwall carbon nanotubes (O‐MWCNTs). The key synthetic precursor hexane‐1, 6‐diaminium adipate and "carbon nanotubate"—"Binary nanotube salt"—was obtained and isolated as stable and easy‐to‐handle solid in over 80% yield and with no nanotube losses. The final hybrid materials of various nanotube loadings were synthesized at 270°C and were easily purified from the homopolymer. Purified hybrids were comprehensively analyzed (yields and grafting ratios, SEM, TEM, FT‐IR) revealing a two‐phase characteristics—individually grafted nanotubes and cross‐linked nanotube material. Isothermal TGA kinetic studies showed that in the "binary salts" diamine and diacid molecules were anchored to the nanotube outer shells and then held electrostatically enabling growth of polymer immobilized on O‐MWCNTs ("grafting‐from" mechanism). Depending on the density and type of nanotube functionalities and filler concentration in the "binary salt, " the O‐MWCNT/Nylon‐6, 6 hybrids can be treated as hybrid material of a proportion of aliphatic polyamide and polyaramide properties. POLYM. COMPOS., 35:523–529, 2014. © 2013 Society of Plastics Engineers